2018
DOI: 10.1021/acs.analchem.8b03773
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Characterization of Charge Heterogeneity of Therapeutic Monoclonal Antibodies Using Strong Cation Exchange Chromatography Coupled to Native Mass Spectrometry

Abstract: In therapeutic monoclonal antibody (mAb) development, charge heterogeneity of a mAb molecule is often associated with critical quality attributes and is therefore monitored throughout development and during QC release to ensure product and process consistency. Elucidating the cause of each charge variant species is an involved process that often requires offline fractionation by ion exchange chromatography (IEX) followed by mass spectrometry (MS) analysis, largely due to the incompatibility of conventional IEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 31 publications
(38 reference statements)
2
60
0
1
Order By: Relevance
“…The use of volatile mobile phases allows the hyphenation of IEC (31)(32)(33)(34), SEC (35)(36)(37), HIC (38,39), RPLC (40), and affinity chromatography (AC)(41-44) techniques to native MS. LC-nMS separates mAb variants prior to the entrance into the MS system, significantly improving sensitivity, dynamic range, and thus the detection of minor variants by limiting competition effects during the MS ionization process. For instance, the direct hyphenation of IEC to MS utilizing low ionic strength eluents on a strong cation exchange (SCX) stationary phase enabled MS data generation from minor mAb variants, and intact mass analysis of various PTMs, such as lysine truncation, glycosylation, and deamidation (mass shift of +1 Da relative to the main peak) (33).…”
Section: Intact Mass Analysis 11 Native Mass Spectrometry (Nms)mentioning
confidence: 99%
“…The use of volatile mobile phases allows the hyphenation of IEC (31)(32)(33)(34), SEC (35)(36)(37), HIC (38,39), RPLC (40), and affinity chromatography (AC)(41-44) techniques to native MS. LC-nMS separates mAb variants prior to the entrance into the MS system, significantly improving sensitivity, dynamic range, and thus the detection of minor variants by limiting competition effects during the MS ionization process. For instance, the direct hyphenation of IEC to MS utilizing low ionic strength eluents on a strong cation exchange (SCX) stationary phase enabled MS data generation from minor mAb variants, and intact mass analysis of various PTMs, such as lysine truncation, glycosylation, and deamidation (mass shift of +1 Da relative to the main peak) (33).…”
Section: Intact Mass Analysis 11 Native Mass Spectrometry (Nms)mentioning
confidence: 99%
“…29,33 Yan et al recently developed a method that combines a generic strong cation exchange (SCX) chromatography step with ultrasensitive online native MS analysis optimized for mAb separation and detection. 34 Bailey et al demonstrated the online WCX-MS analysis of an mAb using a method that incorporates a wellcontrolled pH gradient with high mass resolution and lower adduct formation. 35 Here, we describe increasing sensitivity and the addition of top-down to CEX-MS to achieve site-specific structural information of charge modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in charge state distribution observed for the separated variants can be used to determine their conformation and aggregation state, while UV detection allows their accurate quantification at very low levels. [41][42][43] Hydrophobic interaction chromatography (HIC), which separates proteins based on hydrophobicity and folding state, can also be useful. HIC-MS allowed already the detection of dimers and trimers linked by non-covalent interactions, analyzed under non-denaturing separation and native MS conditions.…”
Section: Introductionmentioning
confidence: 99%